Divorce of Intoxicated Persons in the Islamic Jurisprudence and Afghan Civil Law: An Inductive and Analytical Juridical Study - Aminullah Poya; Bouhedda Ghalia; Mohd Afandi Bin Awang Hamat (International Journal of Islamic Studies Higher Education, 2023)
The phenomenon of divorce in the context of intoxication has drawn limited scholarly attention, necessitating an exploration of its legal implications and theoretical underpinnings. This study employs an inductive and analytical approach, structured into an introduction, three main sections, and a conclusion that encompasses the research findings. The study synthesizes primary legal sources from Islamic jurisprudence, including the Quran and Hadith, alongside relevant provisions of the Afghan Civil Code and pertinent case law. Through a comprehensive examination of Islamic principles and legal precedents, the research delves into the multifaceted issue of divorce within the context of intoxication, addressing pertinent questions regarding the legal capacity and consent of an intoxicated individual to initiate or accept divorce. The analysis also investigates the rights and protections afforded to both parties in such circumstances, considering the overarching objectives of Islamic family law. The study highlights the varying approaches between Islamic jurisprudence and Afghan civil law, identifying potential areas of harmonization or conflict. Drawing on case examples and hypothetical scenarios, the paper further contextualizes the theoretical findings and proposes possible legal reforms to address the complexities arising from the divorce of intoxicated individuals. Ultimately, this research contributes to a deeper understanding of Islamic family law and its application in Afghanistan, while shedding light on the challenges posed by intoxication in the divorce context. The findings of this study may inform legal practitioners, policymakers, and scholars seeking to promote justice, equity, and protection within the realm of family law in both Islamic and Afghan legal systems.